Tool for Assessing Green Initiatives in Library or Green Initiatives in Library: Formulating an Assessment Tool - Razali, Khairul Nazli; Ismail, Farrah Zuhaira (Journal of Social Transformation and Regional Development, 2021)
Amid environmental crisis, the role of built environment sector becomes even more vital as it has a potential to make a significant contribution in reducing greenhouse gas emissions and energy consumption. Library specifically, plays a crucial role in supporting the mission of promoting environmental practice. However, limited rating system explicitly for library’s green initiatives makes it challenging for library to implement these initiatives due to lack of proper guidelines. Hence, this study was conducted to examine existing checklists measuring green initiatives in library and to formulate a checklist for assessing green initiatives in library’s facilities. A systematic review was conducted to establish an assessment checklist, in which three existing checklists related to green initiatives in library were compared and referred to. The assessment checklist developed in this study identifies 107 initiatives related to facilities can be implemented by existing libraries in Malaysia. The result of this study serves as a basis for libraries in Malaysia to environmentally improve its facilities.